Political Economy of Work and Employability Educational Challenges: Boundaryless Careers of Youth and Career Capital - Lin, Mei-Ling (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
The convergence of an aging society, knowledge economy, and professional labor mobility introduces issues for education. Societies are approaching a norm of social politics organized around flexible labor markets and structural exclusion which alters the access to social inclusion through education and employment. The analysis of national education and employment policy is important in the context of a contemporary crisis of capital. The local communities, Taiwan accommodates global capital by deregulating and opening up its markets, takes active interest in the competition for the best brains, and develops a cosmopolitan outlook. The author addresses the rescaling processes affecting Taiwan in which youth are settling. Young people face a world of work filled with uncertainties in the context of intensifying global competition and contractual flexibility. The aim of this paper is to examine some key aspects of social change in Taiwan, which has undergone significant changes in its occupational structure, labor market, economy, and educational provision since the 1980s. The paper has three aims. The first deals with the structural and institutional transformations, and some key aspects in its political economy, labor market and education. The second is concerned with occupational and social mobility patterns and trends, and their association with the changing role of education. Finally, this paper explores the experiences of youth to gain an understanding of the social, political, and cultural factors that impinge on school-to-work and social mobility outcomes. Literature review is utilized to gather some descriptive statistics.